Effects of Recent Concussion on Brain Bioenergetics: A Phosphorus-31 Magnetic Resonance Spectroscopy Study. Issue 4 (December 2015) - Sikoglu, Elif M.; Liso Navarro, Ana A.; Czerniak, Suzanne M.; McCafferty, Joseph; Eisenstock, Jordan; Stevenson, J. Herbert; King, Jean A.; Moore, Constance M.
Abstract : Background: Although clinical evaluations and neurocognitive assessments are commonly used to evaluate the extent of and recovery from concussion, brain bioenergetics could provide a more quantitative marker. The neurometabolic response to a concussion is thought to increase neuronal energy consumption and thus the demand for nucleoside triphosphate (NTP). Objective: We investigated the possible disruption in high-energy metabolism within the prefrontal cortex of college athletes who had either had a concussion within the past 6 months (n=14) or had never had a concussion (n=13). We hypothesized that concussed athletes would have imbalanced brain bioenergetics resulting from increased NTP consumption, and these biochemical changes would correspond to impaired cognitive abilities. Methods: We used phosphorus-31 magnetic resonance spectroscopy to quantify high-energy phosphates. We performed the neuroimaging in conjunction with neurocognitive assessments targeting prefrontal cortex-mediated tasks. Results: Our results revealed significantly lower γ-NTP levels in the athletes after concussion. Although the concussed and non-concussed participants performed similarly in neurocognitive assessments, lower levels of γ-NTP were associated with worse scores on neurocognitive tasks. Conclusions: Our results support the concept of increased energy demand in the prefrontal cortex of a concussed brain, and we found that while neurocognitive assessments appear normal, brain energetics may be abnormal. A longitudinal study could help establish brain NTP levels as a biomarker to aid in diagnosis and to assess recovery in concussed patients.